An Object-Oriented Model for Smart Devices in Internet of Things - Boris Ulitin; Eduard Babkin (Proceedings of the XXth Conference of Open Innovations Association FRUCT, 2018)

(untitled)
The heterogeneity of interconnected devices and communication technologies in the Internet of Things (IoT) domain courses the problem of impossibility to synchronize several different objects in one scheme of the smart space effectively and automatically. Such diversity of technologies results in the need to have special skills in order to reach once created behavior for the smart space. In addition, there are many platforms, which allows to interconnect different devices, but only if they fulfill their protocols. All these lead to the idea, that a new, unified approach to the smart devices representation is needed, which allows to represent objects in a compact form by a platform-independent way. In this article we propose an object-oriented model for representation of the smart devices and demonstrate its efficiency by the simple case of smart space scenes adaptation.